Die deutschsprachige weltliche Liedkultur um 1600 - Renno, Frédérique (Frühe Neuzeit, 2022)
This study examines the transformation that took place in worldly lied culture in German around 1600. Ornate poetry in the vernacular and solo lieder emerged in the sixteenth century and were predominantly developed using Italian elements. Their reception in the middle classes led to the dissemination and valorization of lied culture, and to its codification in literary and music theory.